Making history matter : Kuroita Katsumi and the construction of Imperial Japan - Yoshikawa, Lisa (Harvard East Asian monographs ;, 2017)
"Explores the role history and historians played in imperial Japan's nation and empire building from the 1890s to the 1930s. As ideological architects of this process, leading historians wrote and rewrote narratives that justified the expanding realm. Yoshikawa argues that scholarship and politics were inseparable as Japan's historical profession developed" --